Gender discrimination in Job ads: Theory and evidence - Peter Kuhn; Kailing Shen (Institute for the Study of Labor (IZA), 2010)
We study firms' advertised gender preferences in a population of ads on a Chinese internet job board, and interpret these patterns using a simple employer search model. The model allows us to distinguish firms' underlying gender preferences from firms' propensities to restrict their search to their preferred gender. The model also predicts that higher job skill requirements should reduce the tendency to gender-target a job ad; this is strongly confirmed in our data. We also find that firms' underlying gender preferences are highly job-specific, with many firms requesting men for some jobs and women for others, and with one third of the variation in gender preferences within firm*occupation cells.
Keywords: J71; 330; discrimination; gender; China; internet; search; Personalbeschaffung; Internet; Geschlechterdiskriminierung; Arbeitsmarktdiskriminierung; Arbeitsnachfrage; China